BASIC BIOMECHANICAL CHARACTERISTICS OF THE SECOND PHASE (TSUKURI) OF JUDO THROWING TECHNIQUE OSOTO GARI - Fadil Rexhepi; Željko Hraski (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
In a sample of a total of 11 judoists - one was the Tori (thrower), and the other ten were uke (those who were thrown during the performance of throwing technique), was analyzed the second phase of throwing (tsukuri) judo technique osoto gari. Tori is an active athlete superior quality (master, body mass = 72 kg), and all the other, who were thrown (uke) differ from each other as the weight and height of the body concerned. The average of their body weight was 73.8 kg, which means that it is almost even with body mass of tori. For data collection was used a three-dimensional motion analysis system APAS (Ariel Performance Analysis System). Tsukuri is the phase where occur most actions of reaping leg. The second phase (tsukuri) begins when tori detach his right foot and lasts until the beginning of reaping opponent's leg, on which was concentrated its weight (uke's weight). The parameters that describe the effect of the reaping leg in the second phase of technique osoto gari are crucial for the successful execution of this leg technique. For the analysis of the second phase of the throw were selected 14 variables that describe the position of the body and certain body parts of both athletes, velocity parameters of tori's reaping leg and the duration of this phase (time). The role of the tori's standing leg is to maintain a stable position during this phase, while the other leg quickly and in full force acts reaping. The smallest angle of the knee joint of standing leg during the second phase was 130.84 °. Before the moment of reaping, or detachment of uke`s feet from the mat, standing leg has a tendency to extension in the knee joint, which impacts positively on raising the tori's body center of mass. Height tori's body center of mass at the beginning phase was 87.79 cm. As a result of tori's action by pulling onto uke, but little to his left side, the uke`s center of mass at the end of this phase is moved laterally to 6.10 cm. The results show quite similar values of the distance of the body center of mass of both judoists at the beginning and the end phase, meaning that at the beginning of reaping, uke`s body move slightly to the side, so that the distance between two body center of mass increases and remains almost the same as at the beginning phase. Velocity parameters of tori's reaping leg during reaping are very important factors for a strong effect on the uke`s body or uke`s leg on which this concentrated weight. Maximal linear velocity of the ankle of reaping leg in back direction was 5.05 m / s. Average value of the angular velocity of reaping leg in back direction in the sagittal plane of this phase (before the detachment of uke`s feet) was 198.16 degrees per second (° / s), while maximal angular velocity of the same leg was 316,01 (°/s ). During reaping, or touching his leg with uke`s leg, the knee angle of reaping leg is changed, so its value significantly affect the efficiency of performing technique. Average value of the angle of knee joint (prior to the detachment uke`s feet) was 146.80 °. At this phase occur the most important movements of reaping leg and other parts of tori's body. Therefore, this phase lasts slightly longer than the other phases (0.37 s).